(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article tells about the Kirghiz of the 19th century, who lived in the southern regions of Kyrgyzstan. end - 20th century. was devoted to traditional norms of etiquette in family relations. In this regard, the author collected information from the Leilek, Kara-Suu, and Aksy districts for several years in a row. The article is based on these field materials. This article mainly uses information obtained from informants in Aksy and nearby districts.